(untitled) (Eurasian Journal of Ecology, 2019)
Аrticle discussion of the final opinion and basic formulation for a century in the Kazakh people to form a national, biological, philosophical concepts directly associated with wild animals. For Example, «Bekіre oynaq», «Tasbaqa dauyly», «Qus qanaty», «Qydyr qamshysy», «Kyzyl zhumyrtqa», «Itbalyqtyn kіndіk keserі», «Borі syrgaq», «Donyzdyn tolgagy», «Qoyannyn tolgatuy», «Quralaydin salqyny» «Bugynyn moin jouarry», «Tekeburqyldaq» (tekeburqyl), «Kiіktіn matauy», obviously notable national and basic concepts for direct closely related to natural phenomena. Saying «Tүz tagysy tabigatpen tіldes» above said these national concepts and basic formulation may be a fine example. In addition, a combination of words having to do with wild animals, comparative word in Proverbs and Sayings and legends of their biological and ecological characteristics of specifying data are common. Key words: national concepts, general conclusions, final opinions, phrases, comparative words, proverbs, legends and stories